SYSTEMATIC LITERATURE REVIEW: IMPLEMENTASI MEDIA MIND MAPPING DALAM PEMBELAJARAN IPS DI SMP - Nursamsiyah, Putri; Kusumaningrum, Izky; Safitri, Desy; Sujarwo, Sujarwo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
An important area to continue to improve is education. Education contributes to creating useful humans who become resources who can face all problems. Currently, the role of teachers is very crucial in shaping learning that can realize educational goals. Starting from planning to implementing learning, the teacher must be able to organize it as well as possible. The use of learning media is one of the teacher's efforts to make learning more effective. Teachers can use mind map media in social studies learning in junior high schools. This research is a type of library research, with the method used, namely a systematic literature review. The source of this research is previous research obtained from national journals and 7 articles were used to support this research. Articles were obtained with the help of Google Scholar and this research limits the use of articles published around 2019 to 2023. Based on analysis of previous research articles, the implementation of mind map media has had a positive impact on students, especially in social studies learning in junior high schools. The impacts include increased creativity, increased critical thinking, increased student activity, and improved learning outcomes. So it can be concluded that the application of mind map media makes a positive contribution to creating effective social studies learning for students.